1980
DOI: 10.1542/peds.66.6.859
|View full text |Cite
|
Sign up to set email alerts
|

Reye's Syndrome and Salicylate Use

Abstract: During an outbreak of influenza A, seven patients with Reye's syndrome and 16 ill classmate control subjects were evaluated for characteristics of the patients' prodromal illness and the control subjects illness and for medication usage. Patients during the prodrome and control subjects had similar rates of sore throat, coryza, cough, headache, and gastrointestinal complaints except for documented fever which occurred significantly more often in patients than in control subjects (P = .05). While medications wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…32 One such approach was used by Starko and colleagues 4 years later in a case-control study of seven children with Reye Syndrome which revealed that all seven had been administered salicylates compared with only eight of 16 control subjects. 5 McNaughton and co-workers examined the evidence used to support medicinal product withdrawals in all European Union (EU) member states between 2002 and 2011. 33 They observed that the level of evidence had improved over the 10 year period, with an increased use of case-control, cohort and randomized clinical trial data, and meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 One such approach was used by Starko and colleagues 4 years later in a case-control study of seven children with Reye Syndrome which revealed that all seven had been administered salicylates compared with only eight of 16 control subjects. 5 McNaughton and co-workers examined the evidence used to support medicinal product withdrawals in all European Union (EU) member states between 2002 and 2011. 33 They observed that the level of evidence had improved over the 10 year period, with an increased use of case-control, cohort and randomized clinical trial data, and meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This extremely unusual syndrome was first reported in 1963 but had been first identified 12 years earlier. 4 However, its association with salicylate use in in children with viral illnesses was not recognized until 1980, 5 81 years after aspirin (acetylsalicylic acid) had been introduced into clinical practice. 6 More recently, Nephrogenic Systemic Fibrosis (also known as nephrogenic fibrosing dermopathy) has been described after exposure to gadolinium-based contrast media used for imaging.…”
mentioning
confidence: 99%
“…Killed bacterial vaccines, including diphtheria toxin, pertussis bacteria and tetanus toxin (DPT vaccine), that were first introduced in the 1950s also came to attention because they contained the preservative thimerosal (ethyl mercury), which raised the concern that even the low levels of mercury present in DPT vaccine doses (which were given at 2 months, 4 months, 6 months, 15–18 months and 4–6 years of age) might be neurotoxic. In 1980, epidemiologists at the US Centers for Disease Control reported a link between the use of salicylates for fever management in paediatric patients and Reye syndrome, a fatal hepatic encephalopathy 4 , which led to the substitution of acetaminophen for salicylates. In each of these instances, temporal associations between the introduction of a vaccine or treatment and the apparent increase in the prevalence of autism (a condition that was only rarely diagnosed before the age of 2 years) led to popular concerns that there was a causal link.…”
Section: Changes In Reported Prevalencementioning
confidence: 99%
“…9 The deficit of RCTs forces pediatricians to extrapolate results from studies of adults and apply them to children, which can lead to inappropriate treatments. 10 Historical examples include the use of aspirin, 11 tetracyclines, 12 and chloramphenicol. 13 There are multiple potential barriers limiting enrollment of children in RCTs.…”
mentioning
confidence: 99%